2017
DOI: 10.1111/jcpt.12629
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacodynamic and pharmacokinetic interactions ofHibiscus sabdariffacalyces extracts with simvastatin

Abstract: Aqueous extract of Hibiscus sabdariffa lowered T better than simvastatin and enhanced the antihyperlipidaemic activity of the drug when co-administered at low doses in an animal model. However, aqueous beverage of Hibiscus sabdariffa caused a significant herb-drug interaction resulting in overall reduction in exposure to simvastatin in humans. Caution should thus be placed on clinical judgement or recommendations based on the animal results. Nevertheless, co-administration of the beverage with simvastatin shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…Anthocyanin and quercetin were the components in Hibiscus sabdariffa extract responsible for the antihypertensive effect [2, 5, 9, 10]. However, several studies have found that coadministration of Hibiscus sabdariffa extract with conventional drugs such as acetaminophen, chloroquine, hydrochlorothiazide, simvastatin, and ciprofloxacin produces interactions and influences the efficacy of the primary drug [2, 1114]…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin and quercetin were the components in Hibiscus sabdariffa extract responsible for the antihypertensive effect [2, 5, 9, 10]. However, several studies have found that coadministration of Hibiscus sabdariffa extract with conventional drugs such as acetaminophen, chloroquine, hydrochlorothiazide, simvastatin, and ciprofloxacin produces interactions and influences the efficacy of the primary drug [2, 1114]…”
Section: Introductionmentioning
confidence: 99%
“…Another security risk is herb – drug interactions. Showande et al (Showande, Adegbolagun, Igbinoba, & Fakeye, ) showed that H. sabdariffa beverage and simvastatin coadministration might reduce the absorption, peak plasma concentration, and clearance of simvastatin; additionally, other studies have reported the adverse reactions of H. sabdariffa combined with hydrochlorothiazide and acetaminophen (Hopkins et al, ). Thus, H. sabdariffa safety warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous herb-drug pharmacokinetic interaction studies on Hibiscus sabdariffa aqueous extract showed similar observation. Coadministration of the extract could increase the clearance of acetaminophen, reduce the AUC and Cmax of chloroquine, and increase the clearance as well as reduce the AUC of simvastatin [4,7,8]. However, the coadministration of Hibiscus sabdariffa aqueous extract with captopril does not influence the antihypertensive potency of captopril or its effects on biomarkers of the renin-angiotensin-aldosterone system (RAAS).…”
Section: Effect Of Coadministration Of H Sabdariffa L Aqueousmentioning
confidence: 99%
“…Hibiscus sabdariffa L. (Malvaceae) is an herbaceous shrub grown in tropical areas such as India, Malaysia, Africa, Australia, Florida, the Philippines, and Indonesia [1]. Beverages made from H. sabdariffa L. (variously referred to as "sour tea" or "hibiscus tea") are consumed in many regions of the world and extracts have been used as traditional medicines in numerous cultures [2][3][4]. e consumption of hibiscus tea is growing in popularity owing to accumulating evidence that it can safely reduce blood pressure and serum cholesterol, two major risk factors for cardiovascular disease [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation